Implementation of Clean and Healthy Lifestyles and Social-Physical Distancing by Indonesian Students During the New Normal of Covid-19 Pandemic - Kristiandi, Kiki; Yunianto, Andi Eka; Ningsih, Windi Indah Fajar; Eliza, Eliza; Lusiana, Sanya Anda; Arza, Putri Aulia; Faridi, Ahmad; Yuliantini, Emy (Universitas Islam Bandung, 2023)
Applying a clean and healthy lifestyle is one of the measures to prevent the massive transmission of COVID-19. This study aimed to determine the application of a clean and healthy lifestyle and social-physical distancing carried out by Indonesian students during the new normal of COVID-19. This research was conducted in June 2020 with a cross-sectional study approach, with the number of respondents being 5,924 students in Indonesia. The technique of filling out the questionnaire was done online by Google Forms. Furthermore, respondents would be asked to fill in the available consent letter and answer questions. Based on the results, most respondents were female students with majors in health (3,982 respondents) from undergraduate study programs (2,529 respondents). The place of residence during the pandemic was staying home with the family (2,715 respondents). A clean and healthy lifestyle involves several variables. Those were included touching eyes, nose, and mouth; using hand sanitizer; keeping a mask; opening the door with elbows; touching public equipment; shaking hands; touching with family; washing hands with soap; cleaning; changing clothes; washing masks; personal equipment; and washing hands directly after arrival had a significant relationship, with p<0.005, and p<0.002 for soaking clothes was also significantly related. Therefore, the clean and healthy lifestyle conducted by respondents could be undergone improvement. Also, respondents did not follow the health protocols, which might trigger COVID-19 transmission.